Effect of transboundary water agreements on water and food security of downstream riparian communities: a case study of Indus Waters Treaty - Munir, Sarfraz; Ahmad, Waqas; Hussain, Asghar (2009)
Transboundary water conflicts are awfully crucial in their nature as they not only endanger the food and water security of the riparian communities but also jeopardize the security and existence of the conflicting nations. Any inappropriate action done by upper riparians directly affects the existence of lower riparians. Therefore they need special care to be dealt with. There are 261 international rivers, covering almost one-half of the total land surface which are shared between two or more nations. The management of international waters has been poorly defined in the international arena. In 1947, after the independence of subcontinent, the Indus Basin was divided into two parts between India and Pakistan. Soon after independence India started to halt the river supplies to Pakistan and closed all supplies to the canals which were crossing the India-Pakistan border. India agreed to restore some of the supplies to Pakistan in May 1948, when quite a pro-Indian temporary agreement was signed. It was, however, generally realized that Pakistan could not live without restoration of the full supplies and on this question there could be no compromise. Direct negotiations between the parties failed to resolve the dispute. Negotiations under the World Bank commenced in May 1952. The World Bank planned to divide Indus Basin Rivers into two parts the eastern rivers, under completely Indian control and the western rivers for unrestricted use by Pakistan. Pakistan was not fully convinced and refused to sign until 1958 but ultimately the Treaty was formalized in 1960 after some necessary modifications. Pakistan, on one hand, was deprived a substantial amount of its waters in the Indus Waters Treaty, but on the other, it also got the right of unrestricted use of western rivers. Pakistan also received some assistance (grants and loans) from the World Bank for construction of replacement works for some water storage and diversions. It is evident that the closure or diversion of river flows in the upstream reaches not only affect the downstream river ecology but also puts the downstream irrigated agriculture at stake. This paper highlights the effects of the IWT on water availability and irrigated agriculture in Pakistan. Study finds that though there are some deprivations of surface waters availability to the Pakistan under the IWT but at the same time there are also some improvements in canal water diversions, which are mainly due to the construction of water storage reservoirs. An increase in the cropped area and crop production also has been observed which owes to many other social, economical and technical factors but all this was not possible without reliable irrigation water supplies.